Case study: Analysis of time distribution in Physical Education - Alejandro Muñoz Moreno; Miriam Granado Peinado; Julio Martín López; Jesús Rivilla García (Federación Extremeña de Balonmano; University of Extremadura, 2017)
The use of time effectively as well as practice time is an important aspect for learning the contents of physical education. The aim of this study was to analyze and compare the distribution of time in: Compulsary Secondary Education and 1º Bachillerato. The motor activity and non-activity times were analyzed in 4 sessions at each level. The study involved 166 adolescents. The results showed similar time periods of motor and passive involvement, with no significant difference (p> 0.05) between the two: activity range between 45% and 55%. The higher levels of education (4th ESO and 1 Bachillerato) had higher practice time than the lower levels, with no significant differences between groups (F4, 13 = 31,019; p>0,05). Within the passive time, it was observed that the time devoted to the initial general information occupied at least 19.58%. The results allow to conclude that the level of education does not determine the time of motor activity of the physical education session. On the other hand, the low time of motor activity suggests the need to think about the time dedicated to the weekly physical activity and the education classes.